Effect of special training with rubber ropes in length and step frequency for stages and Performance - Allawy, Abduljabbar Kareem; Ahmed, Omar Saad; Jaffer, Ammar Mosa (International Journal of Psychosocial Rehabilitation, 2020)
The research community represented the players of Diyala clubs of athletics youth of the effectiveness of running 100 meters, who are (12) runners representing Diyala clubs either sample has been chosen deliberate and form of 100% of the original society that was divided into two unequal (experimental and control) and in a random , researcher used the experimental style groups equal terms are equivalent groups in all conditions except the variable pilot, which affects the experimental group to show the difference between the two groups where the researcher conducted a main experiment on a sample of research and of their number (12) runner and on the field of Physical Education College / University Diyala at the fourth afternoon to identify the variables of the study and achievement. After that was filmed runners cameras h number (5) has covered every race distance and then was transferred imaging to the laptop was cutting films by using the program (Hero Soft) and then were analyzed films using the program (Dartfish) were processed statistically using the bag statistical ( Spess) was extract all the variables under study.The researcher reached the following conclusions:–The training ropes rubber have showed clear differences in the stages of the performance of running 100 meters in each of the variable (stride length and step frequency and average speed) for the experimental group compared to controls–For the ropes rubber training has clear impact in the evolution of the size of stride length and reduced the number of steps for a distance of the race compared to the tribal tests.esult of high-speed drills and using the ropes as a means of rubber and different distances led to the development level of completion of running 100 and excitement events for spectators and players in terms of competition and movement performance, whereas the speed key plays role in the development of the completion of this event based on the above, the importance lies in the development of scientific bases correctly when selecting training methods of successful and influential, which contribute to serious the development of achievement of short running distances through the development stages of the performance of that went to the development of researcher training to help speed through the special training through the rubber ropes stride length and frequency so as to reach the goal to be achieved , the study aimed to:-The impact of a curriculum training by rubber cords on the development of stride length and frequency of the 100-meter runners for young people.howing the curriculum training of rubber ropes along the step frequency and runners to the achievement of 100 meters for young peopleThe advantage to influence the training rubber ropes and training in the normal stride length and frequency of runners , achievement of 100 meters and achievement.The hypotheses were as followsThere is a positive effect of training on rubber cords on the stride length, frequency and runner to the achievement of 100 meters for young peopl-There are priority in the influence of special training